PROYEKSI IKLIM PADA LAHAN PERTANIAN PANTI ASUHAN MIFTAHUL JANNAH SEBAGAI UPAYA PERTANIAN ADAPTIF IKLIM - Pradana, Onny; Pradana, Onny Chrisna Pandu; Dwi Putri, Anna; Putri, Sekar Utami; Apriyani, Marlinda (Jurnal Pepadu, 2025)
ABSTRACT Climate change is a global challenge that has significant impacts on various sectors of life, particularly agriculture, which relies heavily on climate conditions. The concept of climate-adaptive agriculture, which involves the use of future climate projections, can serve as one solution to address this issue. This Community Service Program was conducted at the Miftahul Jannah Orphanage in Bandar Lampung City, while the farmland managed by the orphanage is located in Natar, South Lampung District, Lampung Province. The program was implemented in the form of agricultural extension activities (lectures, discussions, and demonstrations) in August 2025. Based on the activities, it can be concluded that: (1) through the lectures and discussions, the knowledge of the orphanage members about climate-adaptive farming practices increased by 27%, and (2) through the demonstration activity, the agricultural land of the orphanage was projected to have an Oldeman Climate Type D2 in the next 20 years (2025–2045). Keywords: Climate Change, Climate Projection, MarkSim, Miftahul Jannah, Oldeman